Evaluation of Physical Stability of Lip Balm Preparation from Ethanol Extract of Tomato Fruit (Solanum Lycopersicum L.) - Suryani Toker; Ratih Arum Astuti (Sean Institute, 2026)
Lips is part skin that has layer thinner than​ part body other so that more prone to experience drought And damage consequence exposure factor environment . One of the efforts that can be made done For guard humidity lips is use of lip balm. Research This aim For formulate lip balm preparation containing extract ethanol fruit tomatoes ( Solanum lycopersicum L.) with addition of vitamin E and evaluate stability physical . Research use method experimental laboratory with four formulas , namely F0 ( without extract tomato ), F1 (3%), F2 (5%), and F3 (7%). Evaluation stability physique covering test organoleptic , homogeneity , pH, power sticky , power spread , and test favorite panelists . Results study show that all lip balm formulas have characteristics good physique​ with semi- solid form , texture soft , and stable aroma . The pH value of the preparation is at on appropriate range of 5.5 –6.3 with physiological pH skin lips . Analysis statistics use test Kruskal –Wallis shows mark significance of 0.538 (p> 0.05 ) which indicates No there is difference significant between formulas. Research This show that extract ethanol fruit tomato can formulated in stable lip balm preparation And potential developed as material active experience in product maintenance lips .